CEP78 is mutated in a distinct type of Usher syndrome. Issue 3 (14th September 2016) - Fu, Qing; Xu, Mingchu; Chen, Xue; Sheng, Xunlun; Yuan, Zhisheng; Liu, Yani; Li, Huajin; Sun, Zixi; Li, Huiping; Yang, Lizhu; Wang, Keqing; Zhang, Fangxia; et al.
Abstract : Background: Usher syndrome is a genetically heterogeneous disorder featured by combined visual impairment and hearing loss. Despite a dozen of genes involved in Usher syndrome having been identified, the genetic basis remains unknown in 20–30% of patients. In this study, we aimed to identify the novel disease-causing gene of a distinct subtype of Usher syndrome. Methods: Ophthalmic examinations and hearing tests were performed on patients with Usher syndrome in two consanguineous families. Target capture sequencing was initially performed to screen causative mutations in known retinal disease-causing loci. Whole exome sequencing (WES) and whole genome sequencing (WGS) were applied for identifying novel disease-causing genes. RT-PCR and Sanger sequencing were performed to evaluate the splicing-altering effect of identified CEP78 variants. Results: Patients from the two independent families show a mild Usher syndrome phenotype featured by juvenile or adult-onset cone–rod dystrophy and sensorineural hearing loss. WES and WGS identified two homozygous rare variants that affect mRNA splicing of a ciliary gene CEP78 . RT-PCR confirmed that the two variants indeed lead to abnormal splicing, resulting in premature stop of protein translation due to frameshift. Conclusions: Our results provide evidence that CEP78 is a novel disease-causing gene for Usher syndrome, demonstrating an additional link between ciliopathy and Usher protein network in photoreceptor cells and inner ear hair cells.